Examination of the association between temperature variability and cardiovascular and respiratory mortality in South Africa, 2006–2016 - Makunyane, Malebo Sephule; Rautenbach, Hannes; Wichmann, Janine (Frontiers in Epidemiology, 2025)
BackgroundEvidence is limited on the impact of temperature variability (TV) on health in low-and-middle-income countries (LMICs), such as South Africa. This study examined the association between TV and cardiovascular disease (CVD) and respiratory disease (RD) mortality in five South African cities.MethodsDaily mortality and meteorological data in five South African cities (Bloemfontein, Cape Town, Durban, Johannesburg, and Gqeberha) were collected from Statistics South Africa and the South African Weather Service for the period 2006–2016. TV was calculated as the standard deviation of the daily minimum and maximum temperatures over the exposure period. City-specific risks were estimated using quasi-Poisson regression models combined with distributed lag nonlinear models, adjusting for potential confounders. A meta-analysis was then conducted to pool the overall estimates across cities. Additionally, stratified analyses by age group and sex were performed to assess effect modification.ResultsA total of 213,875 cardiovascular and 114,887 respiratory deaths were recorded in the five cities during the study period. The risks with increasing TV were higher for RD mortality as compared to CVD mortality. The pooled estimates showed the highest and significant increase in RD mortality of 1.21(95% CI: 1.04;1.38) per an increase in TV at 0–2 days from the 25th to the 50th percentile for all ages combined. The elderly appeared more vulnerable to RD mortality than <65 years age group, with significant mortality risks per increase in TV at 0–2 days (RR = 1.18, 95% CI: 1.04; 1.32),0–3 days (RR = 1.16, 95% CI: 1.04; 1.28) and at 0–7 days (RR = 1.12, 95% CI: 1.02; 1.22) from the 50th to the 75th percentile. A stratified analysis showed the elderly and women as more vulnerable. The pooled results across the five cities suggested no statistically significant TV effect on CVD mortality.ConclusionThis study found a short-term association between temperature variability and respiratory mortality, especially among elderly individuals and women, in five South African cities. No significant effect was observed for cardiovascular mortality. The findings support targeted public health strategies that account for temperature-related risks in vulnerable populations.